Dörflinger, Bernd; La Rocca, Claudio; Louden, Robert; de Azevedo Marques, Ubirajara Rancan, Kant’s Lectures / Kants Vorlesungen, Walter de Gruyter, Berlín, 2015. ISBN 978-3- 11-035147-7 - Herszenbaun, Miguel Alejandro; Martínez, Luciana (Studia Kantiana, 2023)
Dörflinger, Bernd; La Rocca, Claudio; Louden, Robert; de Azevedo Marques, Ubirajara Rancan, Kant’s Lectures / Kants Vorlesungen, Walter de Gruyter, Berlín, 2015. ISBN 978-3- 11-035147-7